Parents’ perceptions about the risk factors associated with bullying behaviour in schools - Mkhonto, Flora; Ramalepa, Tshiamo (Orapuh Journal, 2025)
IntroductionBullying in schools occurs both inside and outside school premises, is repeated over time, and can be an intentional physical, verbal, or emotional act. Bullying is directed at learners who are unable to defend themselves. Millions of children and adolescents are deprived of their fundamental right to education due to bullying in schools. Furthermore, learners worldwide experience bullying, which has significant effects on academic performance, dropout rates, and physical and mental health.PurposeThis study aimed to explore parents' perceptions regarding the risk factors associated with bullying behaviour at a high school in Gauteng, South Africa.MethodsA qualitative approach was employed, using an exploratory, descriptive, and contextual design. The study was conducted in a high school in Gauteng. Participants were purposively selected parents, and data were collected through three focus group interviews. Thematic analysis was used to analyse the data. The sample size consisted of 13 participants across the three focus groups.ResultsThe findings revealed five themes: psychological factors related to bullying, behaviours associated with bullying, environmental factors influencing bullying, and risk factors linked to the relationship between the bully and the victim. There was poor psychosocial awareness of bullying among learners, particularly bullies, who lacked social awareness skills to recognise their own and others' emotions and to respond with empathy.ConclusionThe prevention of bullying can be enhanced by addressing the risk factors that contribute to bullying perpetration, such as anger and aggression. Many children are raised by single parents, parents who abuse alcohol, violent and abusive caregivers, or in poverty-stricken households—all of which contribute to bullying behaviours. Additionally, victims may exhibit certain behaviours that increase their risk of being bullied. A multidisciplinary team—including primary health care nurses, school health nurses, psychiatric nurses, psychologists, psychiatrists, teachers, parents, and social workers—should identify these risk factors and the emotional trauma experienced by children. Early intervention is essential to prevent mental health issues and break the intergenerational cycle of violence.